A randomized open label phase-II clinical trial with or without infusion of plasma from subjects after convalescence of SARS-CoV-2 infection in high-risk patients with confirmed severe SARS-CoV-2 disease (RECOVER): a structured summary of a study protocol for a randomised controlled trial - Janssen, Maike; Schäkel, Ulrike; Djuika, Carine F.; Krisam, Johannes; Stermann, Jacek; Kriegsmann, Katharina; Haberbosch, Isabella; Novotný, Jan Philipp; Weber, Stefan F.; Vehreschild, Maria J. G. T.; Bornhäuser, Martin; Bullinger, Lars; et al. (Trials, 2020)
Primary objectives
Gesehen am 21.11.2024